2005
DOI: 10.1038/sj.bjc.6602457
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Rad51-dependent homologous recombination: implications for the radiation sensitivity of human lung cancer cell lines

Abstract: The aim of the present work was to study the role of Rad51-dependent homologous recombination in the radiation response of non-small-cell lung cancer (NSCLC) cell lines. A dose-and time-dependent increase in the formation of Rad51 and g-H2AX foci with a maximum at about 4 and 1 h after irradiation, followed by a decrease, has been found. The relative fraction of cells with persisting Rad51 foci was 20 -30% in radioresistant and 60 -80% in radiosensitive cell lines. In comparison, a higher fraction of residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 40 publications
3
51
1
Order By: Relevance
“…Ku70, Ku86, and DNA-dependent protein kinase catalytic subunit are key proteins that participate in nonhomologus end joining pathway, which is especially important for repairing the radiation-induced double-strand breaks that are responsible for loss of clonogenic cell survival (20 -22). Down-regulation of these key DNA repair proteins has been linked with an enhanced radioresponse (29,30). In our study, levels of Ku70 and Ku86 proteins were suppressed in A375 cells treated with Vorinostat in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 51%
“…Ku70, Ku86, and DNA-dependent protein kinase catalytic subunit are key proteins that participate in nonhomologus end joining pathway, which is especially important for repairing the radiation-induced double-strand breaks that are responsible for loss of clonogenic cell survival (20 -22). Down-regulation of these key DNA repair proteins has been linked with an enhanced radioresponse (29,30). In our study, levels of Ku70 and Ku86 proteins were suppressed in A375 cells treated with Vorinostat in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 51%
“…(55). Targeting a number of DNA repair proteins such as RAD51, XRCC4 and ATM has also been shown to increase radiation sensitivity in tumour cell lines (56)(57)(58). In our study, tumours could be sub-classified on the basis of expression of genes with roles in DNA repair and there was a numeric better therapeutic response to irradiation in patients with lowest expression of DNA repair genes (Group 1B), and poorer response in patients with highest expression (Group 1A).…”
Section: 5 -------------------------------------------------C -----mentioning
confidence: 73%
“…Previous studies have also shown that the PI3K inhibitor wortmannin can prevent radiation-induced apoptosis and the formation of Rad51 foci in NSCLC (Sak et al, 2005). In addition, there is evidence indicating that c-Abl is involved in increasing Rad51 transcription.…”
Section: Downloaded Frommentioning
confidence: 90%